Pengabdian Mandiri Terintegrasi Dengan Kuliah Kerja Nyata (KKN) Daring di SMK Negeri 1 Berau : Real Work Lectures (KKN) during the Pandemic: A Case Study of the Faculty of Teacher Training and Education of UMKT at SMAN 4 Berau. - Ade Hermawan; Muhammad Haider Ali; Shamila Bashayeva; Syarifah Fitri; Yeni Rahmawati (Wadah Inovasi Indonesia, 2023)
Kuliah Kerja Nyata (KKN) is a fundamental element of the Indonesian higher education system, designed to establish a connection between students and society with the objective of addressing developmental challenges. This article examines the application of KKN (Community Service Program) by the Faculty of Teacher Training and Education at Universitas Muhammadiyah East Kalimantan, specifically at SMAN 4 Berau. The primary emphasis is on the program's adaptation to the challenges posed by the COVID-19 pandemic. In response to the government's decision to enforce social distancing measures and restrict migration, adjustments were made to the KKN program in order to ensure its continued efficacy. The decision to proceed with the KKN program, made by the Faculty of Teacher Training and Education at Muhammadiyah University of East Kalimantan, has been accompanied by certain modifications.